EVALUATION OF QUALITY MANAGEMENT SYSTEM USING ISO 9001:2015 AT STARTUP COMPANY - Luqyana Fitri Anggraeni; Wella Wella; Suryasari Suryasari (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- The Company requires international standards to be recognized by large companies. The international standard that can be used is ISO 9001:2015, were before implementing directly to formal institutions, companies need to conduct a self-assessment on the achievement of ISO 9001:2015 implementation. The ISO 9001:2015 international quality management system is based on ten principles. These principles are used by senior management as a framework that guides the organization towards improving performance. The rating scale consists of Very Poor, Poor, Moderate, Good, and Very Good, which is converted into a maturity level. The implementation of ISO 9001:2015 has been going well, where the average maturity level obtained by The Company is at levels 3 to 4. Keywords: ISO 9001:2015; Maturity Level; Quality Management